The pattern of foot and ankle injury in a tertiary referral hospital in Indonesia: magnitude of traffic accident - Pradana, Ananto S.; Mustamsir, Edi; Agustono, Hary W.; Cahyono, Ganang D.; Bimadi, Mohammad H.; Pandiangan, Ray A. H.; Sukmajaya, William P.; Phatama, Krisna Y.; Hidayat, Mohamad (International Journal of Research in Medical Sciences, 2021)
Background: One of the contributing factors for foot and ankle injury was traffic accidents. A high incidence of foot and ankle injury need to be considered. There is still no adequate information about the epidemiology of foot and ankle injury in Indonesia. This study aims to describe the pattern of foot and ankle injury in Saiful Anwar General Hospital Malang, a tertiary referral hospital in Indonesia. We focused on the distribution of population demography, type of injury, site of injury, the mode of injury, and the treatment of foot and ankle injury. Methods: This cross-sectional study collected the data from the orthopaedic and traumatology department from January 2017 to January 2018. Orava modification classification was used to classify the injury type. The inclusion criteria were trauma patients. The exclusion criteria were the patients who passed away, non-traumatic foot and ankle pathology, refused definitive/all treatment, and unspecified injury site. Results: A total of 304 patients have met the inclusion criteria. Male patients dominated the number of foot and ankle injuries. The majority cause of the injury was traffic accidents (93.4%). The most common injury in this study was fracture (50.3%). Moreover, forefoot was the most common injured site (60.7%). Conclusions: In Indonesia, traffic accidents contribute to foot and ankle injury. The traffic regulation needed to curb the menace of traffic accidents in foot and ankle injury. However, further studies with more databases from multiple centers and evaluate the severity of the injury, the treatment, and the outcome are needed to provide a better study.